Identifikasi Cendawan Mikoriza Arbuskula Dari Perakaran Tanaman Pertanian - Eka Sukmawaty; Hafsan H; Asriani A (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Micorrhyza arbuscula fungi is one of endomicorrhyza group with hiphae stucture called arbuscule. Micorrhyza fungi able to associate with various plants include crop plant. This research aim to know the genus of micorrhyza arbuscule fungi on crop plants root and to know micorrhyza structure on it. The result showed that the highest diversity of micorrhyza was found on potato root, then on strawberry root and the last on tomato root. There are 16 genus was found, they are 11 genus Glomus, 4 genus Acaulospora and 1 genus Ambispora. The arbuscule and vesicle structure was also observed.